Analyzing Primary Social Studies Curriculum of Turkey in Terms of UNESCO Educational for Sustainable Development Theme - YALÇINKAYA, Elvan (European Journal of Sustainable Development, 2013)
These three terms have been used at website of UNESCO: Sustainable development(SD), education for sustainable development (ESD) and the United Nations Decade ofEducation for Sustainable Development (DESD). In this website, it is mentioned that thethree terms have the same goal; creating abetter world for this generation and futuregenerations of all living things on planet Earth. The aim of this study is to analyzePrimary Social Studies Curriculum of Turkeyin terms of UNESCO ESD Theme. Datawas obtained from Social Studies Curriculum. Inthis study, Social Studies Curriculum ofTurkey was discussed in terms of three perspectives which are stated in UNESCO’sFramework for the United Nations Decadeof Education for Sustainable DevelopmentInternational Implementation Scheme (DESD). These three perspectives are; socio-cultural, environmental and economic perspectives. As a result, in this study, it isconcluded that Social StudiesCurriculum should be improvedin terms of ESD. It issuggested that authorities, academics, program developers, teachers should consider themultidisciplinary feature of both Social Studies Curriculum, and education for sustainabledevelopment